The effect of medication safety education program on the knowledge, attitude and practices of registered nurses in a private hospital - Tajuddin, Nur Izzana Ahmad; Kunju, Annamma Kunju; Ahmad, Aini (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Ikatan Dokter Indonesia (IDI), 2025)
Background: Patient safety is crucial in healthcare, with medication being a key component in assessing quality. Medication errors, which are unintended issues in the drug administration process, can occur at any stage—prescribing, dispensing, storing, preparing, or administering and pose serious risks to patients. Defined as accidental failures in the drug-treatment process, these errors contribute significantly to preventable adverse events and public health burdens. Addressing medication errors requires a thorough and comprehensive approach to minimize their impact. Purpose: To assess and enhance nurses' understanding of medication errors, their causes, and preventive strategies through a comprehensive medication safety program. Method: A quantitative, single-group, non-randomized quasi-experimental design with pre- and post-tests. It involved 57 registered nurses from healthcare facilities. Data were collected before and after the program intervention using self-administered questionnaires and objective structured clinical examinations (OSCE). Analysis was performed using SPSS version 22. Results: Significant improvements in nurses' knowledge, attitudes, and practices regarding medication safety. The percentage of participants with